Поняття та сутність механізму правового регулювання захисту прав працівників від незаконного звільнення - Зіноватний, В. В.; Zinovatnyi , V. V. (Юридична наука. - 2020. - № 2, т. 2. - С. 167-174, 2020)
На основі загально-наукових підходів до тлумачення явища «механізм», розкрито зміст та сутність правової категорії «механізм правового регулювання». Побудовано дефініцію поняття механізму правового регулювання захисту прав працівників від незаконного звільнення. Проаналізовано наукові підходи до класифікації елементів механізму правового регулювання. Окреслено структуру механізму правового регулювання захисту прав працівників від незаконного звільнення та встановлено особливості кожного структурного елементу. Зроблено висновок, що забезпечення ефективного функціонування механізму правового регулювання захисту прав працівників від незаконного звільнення є важливим аспектом забезпечення та реалізації гарантованого Конституцією України та нормами чинного законодавства права на працю.

Based on general scientific approaches to the interpretation of the "mechanism" phenomenon, the content and essence of the legal category "mechanism of legal regulation" is revealed. The definition of the concept of the mechanism of legal regulation of the protection of the rights of employees against illegal dismissal has been built. Scientific approaches to the classification of elements of the mechanism of legal regulation are analyzed. The structure of the mechanism of legal regulation of the protection of the rights of employees against illegal dismissal is outlined and the peculiarities of each structural element are established. It was concluded that ensuring the effective functioning of the mechanism of legal regulation to protect the rights of employees against illegal dismissal is an important aspect of ensuring and implementing the right to work guaranteed by the Constitution of Ukraine and the norms of current legislation. The key features through which it is possible to reveal the essence of the mechanism of legal regulation of the protection of the rights of employees against illegal dismissal are the following: first, it is a dynamic element of the legal system, which is aimed at regulating social relations arising in the relevant sphere; secondly, it has a specific purpose: to protect the rights of employees against illegal dismissal; thirdly, it includes a set of elements that complement each other, interact with each other, perform their own tasks and functions, but at the same time are aimed at achieving a single goal; fourthly, it has its own, specific legal instrument and means of its implementation, the effect of which is determined by the specificity of the subject of legal regulation; fifth, has a special subject composition, each representative of which has its own, special labor law status.

Проанализированы понятие и сущность механизма правового регулирования защиты прав работников от незаконного увольнения. Построена дефиниция механизма правового регулирования защиты прав работников от незаконного увольнения. Установлена структура изучаемой категории и выделены ее основные особенности.
The concept and essence of the legal regulatory mechanism for the protection of the rights of employees against illegal dismissal
Keywords: правове регулювання; механізм правового регулювання; захист прав працівників; незаконне звільнення; захист від незаконного звільнення; legal regulation; mechanism of legal regulation; protection of workers' rights; illegal dismissal; protection against illegal dismissal; правовое регулирование; механизм правового регулирования; защита прав работников; незаконное увольнение; защита от незаконного увольнения